Break through the mold: Hyper-IgE syndrome as a vehicle for invasive aspergillosis - Joseph Nordin; Stephen Smetana; Rachel Johnson; Angela Bartosiak; Nicholas Nassif (Respiratory Medicine Case Reports)
Hyperimmunoglobulin E syndrome (HIGES) is a rare immunodeficiency characterized by high levels of immunoglobulin E (IgE) in the setting of various clinical features such as cutaneous candidiasis, asthma, recurrent rashes, and fungal infections. This case describes a 70-year-old male with cachexia and dyspnea found to have a cavitary lesion and aspergilloma, with remarkably high IgE and positive 1,3-β-D-glucan and Aspergillus testing. Herein, we describe the aforementioned case, review the available literature, and hypothesize the connection between invasive fungal infections and HIGES. We hope this discussion helps highlight the importance of a broad differential in chronic dyspnea, including infectious etiologies, and allows for a better understanding of immunologic labs in the setting of fungal infections.